Characteristics of green seaweed salt as alternative salt for hypertensive patients. (May 2019) - Nufus, C; Abdullah, A; Nurjanah,
Abstract: Seaweeds from seashore contain high nutrient and various bioactive compounds that have various beneficial roles such as antioxidant property. Antioxidants can improve health and play a role in preventing the emergence of chronic diseases. This study was aimed to characterize green seaweed salt antioxidant activity. The study consisted of analysis of the mineral, and NaCl content, as well as determination of the antioxidant activity of green seaweed salt by CUPRAC and FRAP method. Different factors affecting salt quality and antioxidant activityincluding types of seaweed (Caulerpa lentillifera and Halimeda opuntia), temperatures (40°C, 55°C and 70°C) and extraction times (10 and 30 minutes) were evaluated. The results showed that the interaction between seaweed, time and temperature did not significantly affect the level of salt content, but significantly affected the Na:K ratio and NaCl content. Salt of C. lentillifera treated at 40°C for 30 minutes showed the highest antioxidant activity measured with FRAP method (137. 07 μmol trolox/g), while salt of H. opuntia treated at 40°C treatment for 30 minutes gave the highest antioxidant activity as measured by CUPRAC method (58.14 μmol trolox/g).